If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 + -1(2m + 3) = 5 + 2m + -16 Reorder the terms: 16 + -1(3 + 2m) = 5 + 2m + -16 16 + (3 * -1 + 2m * -1) = 5 + 2m + -16 16 + (-3 + -2m) = 5 + 2m + -16 Combine like terms: 16 + -3 = 13 13 + -2m = 5 + 2m + -16 Reorder the terms: 13 + -2m = 5 + -16 + 2m Combine like terms: 5 + -16 = -11 13 + -2m = -11 + 2m Solving 13 + -2m = -11 + 2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2m' to each side of the equation. 13 + -2m + -2m = -11 + 2m + -2m Combine like terms: -2m + -2m = -4m 13 + -4m = -11 + 2m + -2m Combine like terms: 2m + -2m = 0 13 + -4m = -11 + 0 13 + -4m = -11 Add '-13' to each side of the equation. 13 + -13 + -4m = -11 + -13 Combine like terms: 13 + -13 = 0 0 + -4m = -11 + -13 -4m = -11 + -13 Combine like terms: -11 + -13 = -24 -4m = -24 Divide each side by '-4'. m = 6 Simplifying m = 6
| 15+0.75x=13+0.50x | | 6x-18=3x+27 | | 6+-1y+5y+6y= | | x+30+2x+15=180 | | 10x-21x=15x-14 | | 4x+11+120=180 | | -7=11+3b | | 9x+8x+10=180 | | 27x-4=30+10x | | 2n^2-9n+7=0 | | 5(x-3)=115 | | 80+22b=30b | | 87=4x+3 | | 10+x=2x-17 | | (x+6)(3x-5)=0 | | -8x+23+10x+23=-6 | | 9x+2=.75(2x+11) | | -11=x-1 | | 18-2g=42 | | Y=3x^2+5x-1 | | -18x-2=-9(2x+1) | | 23-4k=-3k | | 62x+87-6015=43424 | | x+3w+x+3w=96 | | 24+16=24x-10 | | 24-8=8-2x | | 24+8=8+2x | | 8x=7x+12 | | 4x=456 | | x^4+4x^3+2x^2-x=6 | | 3p-7g+14p= | | .18(6)+0.03x=.09(24+x) |